PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KESETIMBANGAN KIMIA - Nova Rilanty; Tita Juwitaningsih (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2020)
This study aims to develop and see the effect of website-based learning media on improving student learning outcomes. The population of this research is all students of grade XI of SMA Panca Budi Medan. Samples were taken by simple random sampling of two classes consisting of experimental class 1 which was taught using website-based media with a problem based learning model and experimental class 2 which was taught using power point media with direct instruction model. Based on the results of data analysis, website-based learning media that have been made have met the eligibility standard with a score of 3.71 out of 4,00 with valid criteria and do not need to be revised. Based on the results of the t test, the tcount data (2.44) is greater than ttable, so the hypothesis can be accepted.. So it can be concluded that the website-based learning media on the chemical equilibrium material made has met the website's eligibility standards; Student learning outcomes using website-based learning media with problem based learning models are higher than student learning outcomes using power point learning media with direct instruction models.